2020
DOI: 10.1111/1365-2664.13606
|View full text |Cite
|
Sign up to set email alerts
|

Disturbances as opportunities: Learning from disturbance‐response parallels in social and ecological systems to better adapt to climate change

Abstract: Disturbances (e.g. fires, floods, windstorms, landslides and tsunamis) are ubiquitous throughout the world. Many social and ecological systems have resilience mechanisms to accommodate and recover from such events. Yet, in an era of directional climate change, adaptation (rather than recovery to the same state) may be the most logical path. In such cases, disturbances, while often unwelcome, may function as opportunities for change. We synthesize the literature on disturbances and adaptation to climate change … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 77 publications
0
10
0
Order By: Relevance
“…We know that ecological crises will recur with increasing frequency, and we need to plan for this new future. Massive ecological disturbances, like megafires, also disrupt prevailing social and professional practices and norms and can be an opportunity for significant change (Buma & Schultz, 2020). The 2019–2020 fires should trigger a state shift in strategic planning and preparedness, creative adaptation, and new models of collaboration.…”
Section: Discussionmentioning
confidence: 99%
“…We know that ecological crises will recur with increasing frequency, and we need to plan for this new future. Massive ecological disturbances, like megafires, also disrupt prevailing social and professional practices and norms and can be an opportunity for significant change (Buma & Schultz, 2020). The 2019–2020 fires should trigger a state shift in strategic planning and preparedness, creative adaptation, and new models of collaboration.…”
Section: Discussionmentioning
confidence: 99%
“…Interactions and feedbacks between global disturbance patterns are a major threat to the integrity and function of ecosystems and can result in unprecedented ecological impacts (Burton et al 2020). While this topic has received interest worldwide (C ôté et al 2016, Barnes et al 2017, Buma and Schultz 2020, research on the interactive nature of biodiversity responses to disturbances is limited, but critical for the conservation of ecosystems in a period of rapid, global, environmental change. Based on data from a decade of extensive empirical, multifaceted research, we have demonstrated that the number of standreplacing disturbances and stand age can impact forest structural elements and biodiversity, both directly and indirectly through ecological interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Identified obstacles for future natural disturbances could in a long-term perspective generate new types of negative aspects for the national parks. According to Buma, Schultz and Leverkus [4] natural disturbances have the potential to create opportunities for adaptation towards climate change within social and ecological systems. After a natural disturbance such as fire, the environmental area will develop according to new premises, such as increased temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, fire has the ability to increase the diversity of both flora and fauna species due to mixed-severity regimes in both temporal and spatial variability [3]. Another example is that disturbances could contribute to national parks' adaptation to climate change and increased temperatures [4]. The importance of natural disturbances for biodiversity is well-documented in the disturbance ecology literature [5][6][7][8], often with a more specific demarcation such as the contribution of fire to forest development [3,[9][10][11][12].…”
Section: Introduction-natural Disturbances and Conservation Strategiesmentioning
confidence: 99%